Role of sensory nerves in the rapid cutaneous vasodilator response to local heating in young and older endurance-trained and untrained men - Tew, G. A.; Klonizakis, M.; Moss, J.; Ruddock, A. D.; Saxton, J. M.; Hodges, G. J. (Experimental Physiology, 2011)
The ability to increase skin blood flow (SkBF) rapidly in response to local heating is diminished with advanced age; however, the mechanisms are unclear. The primary aim of this study was to investigate the role of sensory nerves in this age-related change. A secondary aim was to investigate the effect of aerobic fitness on sensory nerve-mediated vasodilatation in young and aged skin. We measured SkBF (using laser Doppler flowmetry) in young and older endurance-trained and untrained men (n = 7 in each group) at baseline and during 35 min of local skin heating to 42°C at two sites on the ventral forearm. One site was pretreated with topical anaesthetic cream to block local sensory nerve function. Cutaneous vascular conductance (CVC) was calculated as SkBF divided by mean arterial pressure and normalized to maximal values (CVCmax) achieved during local heating to 44°C. At the untreated site, the rapid vasodilatation during the first ~5 min of local heating (initial peak) was lower in the older untrained group (68 ± 3%CVCmax) compared with all other groups (young trained, 76 ± 4%CVCmax; young untrained, 75 ± 5%CVCmax; and older trained, 81 ± 3%CVCmax; P < 0.05). Sensory nerve blockade abolished these differences among the groups (P > 0.05). The contribution of sensory nerve-mediated vasodilatation was lower in the older untrained group compared with all other groups (P< 0.05). Our results suggest that the age-related decline in the rapid vasodilator response to local heating in human skin is explained by diminished sensory nerve-mediated vasodilatation. These findings also indicate that this age-related change can be prevented through participation in regular aerobic exercise.